BEING A TRANSVESTITE IN THE CONTEXT OF CIS HETERONORMATIVITY: A GESTALTICAL VIEW - Castilho, Viviane Barbosa da Cruz (Seven Editora, 2025)
This study addresses the transvestite experience in the context of cis-heteronormativity, based on a Gestalt therapy analysis, highlighting the impact of marginalization and social invisibility experienced by this population, in addition to the social and political achievements for the inclusion of the LGBTQIA+ community. DOI: https://doi.org/10.56238/sevened2024.035-006